Religion and ecological sustainability in China - Miller, James 1968-; Yu, Dan 1962-; Veer, Peter van der 1953- (Routledge contemporary China series, 2014)
"This book sheds light on the social imagination of nature and environment in contemporary China. It demonstrates how the urgent debate on how to create an ecologically sustainable future for the world's most populous country is shaped by its complex engagement with religious traditions, competing visions of modernity and globalization, and by engagement with minority nationalities who live in areas of outstanding natural beauty on China's physical and social margins. The book develops a comprehensive understanding of contemporary China that goes beyond the tradition/ modernity dichotomy, and illuminates the diversity of narratives and worldviews that inform contemporary Chinese understandings of and engagements with nature and environment"..